International Law as Constructive Resistance towards Peace and Justice - Seta, Makoto, (International Law E-Books Online, Collection 2024., 2024)
Professor Toshiki Mogami , the featured figure of this memorial edition, has developed his academic career in international law and politics. Professor Mogami's original normative and analytical framework is characterized by himself as Jus Contra Anarchism et Oligarchism: international law against interstate and institutionalised violence . The editors extract the very essence of his teachings from Professor Mogami's masterpieces, specifically, International Law as Constructive Resistance towards Peace and Justice .